2017
DOI: 10.1007/s13224-017-1036-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Platelet Distribution Width (PDW) and Plateletcrit in the Assessment of Nonthrombocytopenic Preeclampsia and Eclampsia

Abstract: Platelet indices showed a significant variation along with the severity of the disease. Platelet indices, especially PDW and plateletcrit, can be used along with platelet count to evaluate the severity of preeclampsia and eclampsia instead of relying on platelet count alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…In addition, MPV also served as a clue for the reflection of platelet activation in DM regardless of the diabetic retinopathy stage [ 25 ]. In addition to MPV, additional platelet indices PDW and PCT calculated by PC and MPV have been reported to play roles in atherosclerosis and thrombosis, as well in TB [ 26 ]. Higher PDW and PCT values developed frequently in patients with PTB with a strong correlation between phase reactants and acute thrombocytosis [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MPV also served as a clue for the reflection of platelet activation in DM regardless of the diabetic retinopathy stage [ 25 ]. In addition to MPV, additional platelet indices PDW and PCT calculated by PC and MPV have been reported to play roles in atherosclerosis and thrombosis, as well in TB [ 26 ]. Higher PDW and PCT values developed frequently in patients with PTB with a strong correlation between phase reactants and acute thrombocytosis [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…As plateletcrit is an indicator of platelet activity in blood, low plateletcrit reflects low platelet activity. 5 It has been found that plateletcrit can be used instead of platelet counts alone to determine if the patient needs platelet transfusions and is a useful screening tool for detection of platelet quantitative disorders. Plateletcrit is a measure of the total platelet mass and seems to be more clinically useful than being just an additional value to the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…PDW was found to be the 2 nd most reliable biomarker for pre-eclampsia with AUC of 0.984, sensitivity of 93.4%, and specificity equal to MPV (93.3%) in our study. Even in nonthrombocytopenic PE, PDW has been considered a very important parameter, and a reflection of ongoing platelet activation [15]. Thalor et al, Sitotaw C, Karateke et al also found a significant high MPV, PDW, P-LCR in PE women and rise of these indices correlated positively with mean blood pressure [16,17,18].…”
Section: Ceyhan Et Al Alsheeha Et Al and Altinbas Et Al Found No Sigmentioning
confidence: 99%